GAMBARAN EFEKTIFITAS PENERAPAN 5 STANDAR OPERASIONAL PROSEDUR (SOP) PELANGGAN DI PBF BINA PRIMA SEJATI JAKARTA BARAT - Brahmono, Angga; Saragi, Sahat; Andayani, Nurita (Jurnal Riset Kefarmasian Indonesia, 2023)
The CDOB guidelines state that in implementing CDOB, one must have an SOP. SOP formulation as a benchmark in assessing the effectiveness and efficiency of agency performance in implementing its work program. The principle of preparing SOPs must also be oriented to the parties served so that they can provide satisfaction to users. It is important for PBF to pay attention to the quality of services provided to pharmacies because it can lead to satisfaction and a positive attitude from customers. The purpose of this study was to determine the effectiveness of implementing 5 customer SOPs at PBF Bina Prima Sejati. The method used in this research is descriptive method with observation. The results of the study showed that the results of the SOP for distributing drugs to new pharmacies were 93.65% carried out by officers; SOP for handling customer complaints has only been implemented 43.81%; SOP for handling counterfeit and suspected counterfeit drugs has only been implemented 80.47%; The SOP for handling new returned drugs was 98.64% carried out by officers and the SOP for handling new recalled drugs was 89.68% carried out by officers. Overall 5 SOPs related to new customers 81.25% are carried out by officers. If it is seen that the effective implementation of the SOP must be 100%, then the implementation of the 5 customer SOPs is not effectively carried out by officers.